2018
DOI: 10.2139/ssrn.3238048
|View full text |Cite
|
Sign up to set email alerts
|

The Digit Ratio (2D:4D) and Economic Preferences: No Robust Associations in a Sample of 330 Women

Abstract: Many studies report on the association between 2D:4D, a putative marker for prenatal testosterone exposure, and economic preferences. However, most of these studies have limited sample sizes and test multiple hypotheses (without preregistration). In this study we mainly replicate the common specifications found in the literature for the association between the 2D:4D ratio and risk taking, the willingness to compete, and dictator game giving separately. In a sample of 330 women we find no robust associations be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…This makes present results relatively less reliable. Last, to have in mind, other reports found no significant association between variation in digit ratios and variations in altruism [42,60], which suggests that that relationship seems rather unreliable.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This makes present results relatively less reliable. Last, to have in mind, other reports found no significant association between variation in digit ratios and variations in altruism [42,60], which suggests that that relationship seems rather unreliable.…”
Section: Discussionmentioning
confidence: 90%
“…In the heart of Gender Roles Theory, authors recognize that the effects of gender roles on behavior could be modulated by pre-and post-natal hormonal processes [44,45], meaning that, as it has been shown for other social preferences such as cooperation [58], norm compliance may be affected by the interaction of social and biological events. In fact, various studies have found a relationship between people´s digit ratios and their generosity in DGs (briefly reviewed in [59] but also see 42,60). However, decisions in the DG may not be straightforward to interpret.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, studies on the associations between 2D:4D and economic behavior usually work with small samples and they usually do not register their pre-analysis plans beforehands. To the best of our knowledge, Parslow et al (2019) is the only study which has a prior pre-analysis plan registered. It gets even more challenging to reach a consensus on whether 2D:4D actually correlates with certain economic decisions due to possible publication biases, researchers' degrees of freedom and false positive results.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, they did not observe any significant relationship between risk aversion and 2D:4D. 2 The recent study of Parslow et al (2019) which uses an extended and incentivized version of the task also reports null results from a large sample of women. In (Gneezy and Potters 1997) also produced conflicting results: High 2D:4D is associated with higher risk aversion in Dreber and Hoffman (2007) while Apicella et al (2008) could not show any significant relationship.…”
Section: D:4d and Risk Aversionmentioning
confidence: 97%
“…Also, in the context of dictator game, Galizzi and Nieboer [2015] discovered an inverted U-shaped relationship between the right digit ratio and allocation level, which differs from the negative monotonic relationship noted in Millet and Dewitte [2009]. In another study of dictator game, Parslow et al [2019] find no significant evidence between the dictator's digit ratio and allocation level. Brañas-Garza et al [2019] also report no robust relationship between the digit ratio and generosity, bargaining, and trust-related behaviors in a dictator game, ultimatum game, and trust game.…”
Section: Digit Ratio In Economic Gamesmentioning
confidence: 99%